THE ROLE OF LEGAL POLICY IN THE MANAGEMENT AND PROTECTION OF NATURAL RESOURCES IN INDONESIA - Susandi, Rizki Arya (Communale Journal, 2025)
Management and protection of natural resources (SDA) in Indonesia face major challenges, especially related to environmental degradation due to unsustainable exploitation. Legal policy plays an important role as a basis for regulating the use of SDA, environmental protection, and law enforcement against violations. Although Indonesia has various laws and regulations governing the management of SDA, such as the Forestry Law, Mineral and Coal, and environmental protection, their implementation is still hampered by weak supervision, coordination between institutions, and conflicts of interest between economic development and environmental conservation. This study uses a qualitative approach with descriptive analysis through literature studies, interviews, and field observations to identify the role of legal policy in the management of SDA and the factors that influence the sustainability of ecosystems in Indonesia. The results of the study indicate that effective legal policy must be able to balance economic interests and environmental conservation with clear regulations, strict supervision, and synergy between related institutions. Thus, legal policy can be a strategic instrument in realizing sustainable management of SDA and optimal environmental protection in Indonesia.